1990
DOI: 10.1099/00207713-40-4-443
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic and Phylogenetic Studies on a New Taxon of Budding, Hyphal Proteobacteria, Hirschia baltica gen. nov., sp. nov.

Abstract: Four strains of budding, hyphal bacteria, which had very similar chemotaxonomic properties, were isolated from the Baltic Sea. The results of DNA-DNA hybridization experiments, indicated that three of the new isolates were closely related, while the fourth was only moderately related to the other three. Sequence signature and higher-order structural detail analyses of the 16s rRNA of strain IFAM 141gT (T = type strain) indicated that this isolate is related to the alpha subclass of the class Proteobacteriu. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
56
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 44 publications
1
56
0
1
Order By: Relevance
“…1a), similar to species of the genera Hirschia (Schlesner et al, 1990) and Hyphomonas (Pongratz, 1957;Moore et al, 1984;Weiner et al, 2000). Vegetative cells produced prostheca 0.06-0.1 mm in diameter and a bud formed at the hyphal tip.…”
Section: Characteristic 1mentioning
confidence: 54%
See 2 more Smart Citations
“…1a), similar to species of the genera Hirschia (Schlesner et al, 1990) and Hyphomonas (Pongratz, 1957;Moore et al, 1984;Weiner et al, 2000). Vegetative cells produced prostheca 0.06-0.1 mm in diameter and a bud formed at the hyphal tip.…”
Section: Characteristic 1mentioning
confidence: 54%
“…Catalase and oxidase activities were tested with 3 % (v/v) Schlesner et al, 1990 and the present study). +, Positive; 2, negative.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The genus Hirschia was first proposed by Schlesner et al (1990) to accommodate a single novel species, Hirschia baltica, which includes budding and hyphal strains of the class Proteobacteria, and a second species of the genus, Hirschia maritima, has been described (Kang & Lee, 2009). Phylogenetic analysis based on 16S rRNA gene sequences showed that the genus Hirschia belongs to the family Hyphomonadaceae of the Alphaproteobacteria (Lee et al, 2005;Lee et al, 2007;Kang & Lee, 2009).…”
mentioning
confidence: 99%
“…Phylogenetic analysis based on 16S rRNA gene sequences showed that the genus Hirschia belongs to the family Hyphomonadaceae of the Alphaproteobacteria (Lee et al, 2005;Lee et al, 2007;Kang & Lee, 2009). Members of the genus Hirschia have been isolated from seawater of the Baltic Sea and the Pacific Ocean (Schlesner et al, 1990;Kang & Lee, 2009). In this study, we describe a bacterial strain, designated M-M23 T , which was isolated from seashore sediment collected at Geoje island of the South Sea, South Korea.…”
mentioning
confidence: 99%